2014
DOI: 10.1007/s12032-014-0867-x
|View full text |Cite
|
Sign up to set email alerts
|

The difference in miR-21 expression levels between invasive and non-invasive breast cancers emphasizes its role in breast cancer invasion

Abstract: MicroRNA-21 (miR-21) overexpression is characteristic for various types of tumors, but it is still unknown whether its expression levels differ between invasive and non-invasive breast carcinomas. The main goal of the study was to determine the difference in miR-21 expression among normal tissue, non-invasive, invasive with non-invasive component, and pure invasive breast cancer samples, to explain its potential role and significance in breast cancer invasiveness. The second goal was to propose miR-21 as molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 28 publications
2
28
0
Order By: Relevance
“…According to those findings and findings from other previous study , (Petrović et al ,2014) miR-21 is a potential biomarker for breast cancer invasion, rather than carcinogenesis and that it might be great biological marker for regrouping the patients with different receptor status. Another examined miRNA is miR-let7c which was highly significant down regulated in early stages breast cancer with p-value 0.0160.…”
Section: Discussion:-supporting
confidence: 72%
“…According to those findings and findings from other previous study , (Petrović et al ,2014) miR-21 is a potential biomarker for breast cancer invasion, rather than carcinogenesis and that it might be great biological marker for regrouping the patients with different receptor status. Another examined miRNA is miR-let7c which was highly significant down regulated in early stages breast cancer with p-value 0.0160.…”
Section: Discussion:-supporting
confidence: 72%
“…29,30 Moreover, previous findings have found a direct correlation between miR-21 levels and the metastatic dissemination of human BC tumor samples. [31][32][33] Our findings revealed that Stat3 regulates ErbB-2 expression and co-opts its nuclear function to induce miR-21 and BC metastasis, highlighting Stat3 and NErbB-2 as novel targets to block metastatic dissemination in MErbB-2-positive BC.…”
Section: Introductionmentioning
confidence: 73%
“…miR-21 is known to play a role in invasion based on its ability to downregulate PDCD4 (Asangani et al, 2008), RECK and TIMP3 (Gabriely et al, 2008) (Zhu et al, 2008), and SULF1 (Bao et al, 2013). A recent study reported higher miR-21 in invasive ERα+/PR+, but not ERα-/PR−, breast tumors (Petrović et al, 2014). Another study reported that thyroid hormone (T 3 ) stimulated cell migration and invasion of HepG2 cells stably expressing thyroid hormone receptors α1 (TRα1) and TRβ1 by down regulating TIAM1 (Huang et al, 2013).…”
Section: Discussionmentioning
confidence: 96%